Evaluation of the American College of Surgeons National Surgical Quality Improvement Program Risk Calculator to predict outcomes after hysterectomies. Issue 3 (12th January 2022) - Hamade, Sara; Alshiek, Jonia; Javadian, Pouya; Ahmed, Sushma; McLeod, Francine N.; Shobeiri, S. Abbas
Abstract: Objective: To evaluate the American College of Surgeons (ACS) surgical risk calculator's reliability in predicting outcomes in hysterectomies. Methods: This is a prospective cohort study at a large community‐based hospital. Twenty‐one preoperative and postoperative criteria were abstracted from the electronic medical record and entered into the online ACS calculator to determine a risk score. Logistical regression was used to determine the association between risk score and actual outcome. The prediction capability was analyzed with c‐statistic, Hosmer‐Lemeshow, and Brier score. Results: A total of 634 hysterectomies were performed during the study period from January to April 2019. Patients were predominantly 55 years old, white (53%) and overweight (body mass index 30). Predicted perioperative adverse events were significantly higher than actual adverse events across all domains. In all, 54/634 (8.5%) patients experienced postoperative urinary tract infection. C‐statistics for return to operating room, renal failure, and readmission were 0.607 (95% C Statistic index [CI] 0.370–0.845), 0.882 (95% CI 0.802–0.962), 0.637 (95% CI 0.524–0.750), respectively. Brier scores approached one in all categorical domains. Conclusion: The ACS surgical risk calculator holds the promise of predicting postoperative complications or length of stay for patients undergoing hysterectomy. Further adjustment to this tool is required before it can be advocated for use in the clinical setting. Abstract : The ACS NSQIP surgical risk calculator is a moderate predictive tool for postoperative complications for patients undergoing hysterectomy.